The Effect of the Non-Assertive Services of the Auditor on the Independence: the Case of IRAQ - Mohammed Yaqoub Al-Otaibi, Raed (International Journal of Psychosocial Rehabilitation, 2020)
The demand for non-affirmative auditing services, such as requesting administrative consulting, to maintain clients with a view to continuity, as well as the emergence of small and medium-sized companies, needed those who organize their work and keep their books, which called on audit firms to provide these services, as well as design accounting information systems, and in an environment of intense competition between audit offices and beneficiaries. In that there is a lack of specialized offices in this type of service that aims to remedy the shortage on the one hand and improve the efficiency of the audit work on the other hand, and that also requires studying its impact on the independence of the auditor because independence represents the backbone of the audit profession The breach thereof will affect its reliability and integrity, as well as the lack of confidence in the financial data. For the purpose of indicating the effect size, a questionnaire was distributed and the study hypothesis was tested by using the mono-variance analysis test to test the differences in the opinions of the study sample about the extent of the impact of non-affirmative services on the independence of auditors at the significance level of 0.05 and it turns out The calculated value of F for all axes combined is 0.969 and is less than the tabular value of F equal to 2.45, which means accepting the research hypothesis that providing non-confirmatory services with regular audits to the same or other entity affects the independence of the auditor For users confidence in his reports.